Extreme heat in Koudougou, Burkina Faso: Analysing trends, community perceptions and migration measures - Yo Boureima; Yameogo Joseph; Sanou Korotimi; Yanogo Pawendkisgou Isidore (Glasnik Srpskog Geografskog Društva)
Climate change is having a profound impact on urban population in the Sahel region, particularly in Burkina Faso, affecting various aspects of daily life. Koudougou, the third largest city in the country, is not exempted. The aim of this article is to examine the main coping strategies of the inhabitants of Koudougou in the face of increasing heat waves. To this end, temperature data for the hottest months (March, April and May) from 1981 to 2024 were analysed to identify climate trends. These data were first subjected to a normality test, then analysed using linear regression and standardised temperature anomaly (STA) methods. At the same time, a survey was conducted among the population to assess the impact of this phenomenon on their daily lives. The results showed that temperatures in Koudougou have increased significantly in recent years and are perceived as high (38.04%) or very high (40.97%) by most of the respondents. This situation is a serious threat for the population wellbeing as it is causing health problems and reducing the productivity of the population. Residents are developing adaptations strategies by redesigning their houses and adopting individual behaviours, such as drinking more water or wearing light clothing, although they often consider these measures to be ineffective. As the effects of climate change on vulnerable regions is projected to increase, awareness raising should be developed through social media, television and radio channels to promote adaptation best practices.